Resirculating Aquaculture System (RAS) Technology Applications in Indonesia : A Review - Adinda Kinasih Jacinda (Jurnal Perikanan dan Kelautan, 2021)
Increasing aquaculture production will increase land use and environmental pollution, especially water quality for cultivation. Resirculating Aquaculture System is a solution in sustainable cultivation that can produce continuous production by minimizing its impact on the environment. The working principles of RAS include the process of solid waste disposal, biofiltration, degassing / CO¬2 stripping, aeration, and disinfection. Based on literature studies, the use of RAS technology in Indonesia has been carried out both on a small scale such as aquaponics and on a large scale in several Balai Sulawesi, Yogyakarta and Aceh to the application of integrated technology in RAS systems such as microbubble and Immuno-Probiocirculation System (SI-PBR). RAS implementation management includes the selection of fish species, selection of feed, the cultivation system used, the filters used and the shape of the cultivation pond. Although the RAS system involves high capital investment and risk factors, this can be balanced with the production of superior quality fish / shrimp without disruption anywhere and anytime.